Characterization and Antibacterial Activity Test of Hydroxyapatite (HAp) from Chicken Eggshell against Lactobacillus acidophilus Bacteria - Imelda Wadu; Hartati Soetjipto; Margareta Novian Cahyanti (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2017)
The purposes of this study were to characterize Hydroxyapatite (HAp) bioceramics which synthesized from local chicken and broiler eggshell using FTIR, and to determine HAp antibacterial activity with the highest content of calcium-phosphate (HAp from broiler chicken eggshell) using paper disc method. Characterization of HAp from local chicken eggshell using FTIR showed peaks for PO43- functional group on the wavelength 1040.08, 608.46 and 568.67 cm-1; OH- functional group on the wavelength 3426.39 and 2880.46 cm-1; CO2 functional group on the wavelength 2142.91 cm-1; and CO32- functional group on the wavelength 1653.64 cm-1. Whereas broiler chicken eggshell HAp showed peaks for PO43- functional group on the wavelength 1044.40, 604.13 and 568.66 cm-1; OH- functional group on the wavelength 3419.61 and 2838.35 cm-1; CO2 functional group on the wavelength 2086.69 cm-1; and CO32- functional group on the wavelength 1653.64 cm-1. HAp antibacterial activity test against caries bacteria L. acidophilus gives the positive results either for the lowest test dose (5μg/μL) or the highest test dose (75μg/μL), which was characterized by the formation of diameter inhibitory area 22.93±0,066 and 33.08±0,031 mm (strong category of >20 mm), respectively. The characterization of HAp from local chicken and broiler chicken eggshell using FTIR confirmed the presence of HAp compounds, and the antibacterial activity test result of HAp synthesized from broiler chicken eggshell indicates a positive and strong antibacterial power.